Genetic Stability The Protein Encoding Envelope (E) Genes Dengue Virus Serotype-4 Passaged in Vero Cell As A Candidate Chimera Vaccine Material - deya karsari (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
This study aims to analyze genetic stability of the gene encoding the envelope protein (E) dengue virus serotype-4 passaged in vero cells, Denv-4 passaged in vero cells serially then continued with RNA extraction at passage 0, 10, 20, 30, 40 ,50 , and 60, and then continued with two step PCR and amplification, and sequencing then analyze the nucleotide stability with BLAST and MEGA 5 software. The result shows that there are many variable site in nucleotide and amino acid with high mutation rate 57.4% for nucleotide and 71.9% for amino acid ,while the similarity between passages are high ranging from 91% - 98%. The conclusion for this study is Denv-4 after analyzed shows that the gene encoding protein E has many variable site but high in similarity.